Sustainable tourism development with special reference to the European Union - Milicević, Snezana; Podovac, Milena; Jovanović, Dusko (Hotel and Tourism Management, 2013)
Tourism is the world’s leading service industry. At the end of the last century it became clear that tourism has a significant impact on employment growth, foreign exchange earnings, balanced regional development and it indirectly generates benefits for other economic activities. The basics for the tourism development are natural attractiveness. With the development of mass tourism there has been uncontrolled exploitation of natural resources, which are primarily reflected in the decline in the quality and the ability to restore them. Contemporary trends in the tourism market indicate the existence of a growing demand for naturally preserved and ecologically clean area. This trend has caused the need to raise awareness of the importance of the links between tourism and the environment. Align development of tourism and conservation of natural resources has been established thanks to the adoption and application of the principles of sustainability. This paper presents the basic principles of sustainable tourism development. The aim of paper is to highlight the importance of sustainable tourism development of the European Union. The emphasis is on the analysis of sustainable tourism development, as well as policies and programs relating to exercise responsible behavior towards the natural environment that the European Community has been implementing.